Role of parameter adaptation in chaotic communication. (2015) - Dwivedi, Arti; Mittal, Ashok Kumar; Dwivedi, Suneet
A chaos shift keying (CSK) scheme for secure communication of binary messages is proposed, in which two identical hyper-chaotic systems are synchronised in a time less than the time scale of their chaotic oscillations using complete replacement, feedback control and parameter adaptation. It is shown that this scheme is more secure compared to other similar schemes because coding parameter of the transmitting system changes so rapidly that an intruder cannot infer any information about the attractors corresponding to the two coding parameters. An extended scheme of secure communication based on arbitrary chaotic systems is also presented. This gives the sender a handle for making changes at the transmitting end without having to convey this information to the receiver, thereby significantly enhancing the security. Salient features of standard cryptology are presented and the cryptological aspects of the proposed chaotic communication scheme are analysed.